2019
DOI: 10.2105/ajph.2018.304883
|View full text |Cite
|
Sign up to set email alerts
|

The National Institute on Minority Health and Health Disparities Research Framework

Abstract: We introduce the National Institute on Minority Health and Health Disparities (NIMHD) research framework, a product that emerged from the NIMHD science visioning process. The NIMHD research framework is a multilevel, multidomain model that depicts a wide array of health determinants relevant to understanding and addressing minority health and health disparities and promoting health equity. We describe the conceptual underpinnings of the framework and define its components. We also describe how the framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
426
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 504 publications
(433 citation statements)
references
References 17 publications
6
426
1
Order By: Relevance
“…According to The Surgeon General's Call to Action to Support Breastfeeding , African American infants experience breastfeeding disparities, regardless of the socioeconomic status they are born into . In fact, as this scoping review was being completed, the National Institute on Minority Health and Health Disparities led a 2‐year interprofessional scientific visioning process to examine ways to reduce racial health disparities . To close the disparity gap, the authors suggested strategies to inform research that facilitates successful adaptation and equitable implementation and delivery of evidence‐based interventions that reduce health disparities …”
Section: Discussionmentioning
confidence: 99%
“…According to The Surgeon General's Call to Action to Support Breastfeeding , African American infants experience breastfeeding disparities, regardless of the socioeconomic status they are born into . In fact, as this scoping review was being completed, the National Institute on Minority Health and Health Disparities led a 2‐year interprofessional scientific visioning process to examine ways to reduce racial health disparities . To close the disparity gap, the authors suggested strategies to inform research that facilitates successful adaptation and equitable implementation and delivery of evidence‐based interventions that reduce health disparities …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the National Institute of Minority Health and Health Disparities research framework [21], multilevel predictors of interest included individual-level age, sex, race, ethnicity, and smoking status, and ZIP code linked contextual-level rural urban (RUCA) classification, and neighborhood disadvantage quartile. We used the Area Deprivation Index (ADI), a neighborhood disadvantage metric encompassing 17 education, employment, housing quality, transportation, and poverty measures to match from 69 million nine-digit ZIP postal code census block groups, i.e., "neighborhoods" of approximately 1500 people [19,20,25].…”
Section: Predictors and Covariatesmentioning
confidence: 99%
“…We hypothesized that Black patients and those residing in highly disadvantaged neighborhoods would have lower retention in care because of the multitude of socioeconomic, access, and other adverse social determinants of health that such residents face [21][22][23]. The objectives of this study were to validate an urban lupus cohort, to create metrics for retention in care, and to examine how race and other social determinants of health predict lupus retention in care.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this goal, we have available a plethora of pragmatic tools including conceptual frameworks that consider context, multi-level influences and facilitate transdisciplinary approaches in cancer education. Examples include applications of longstanding models and approaches such as the socioecological model [8,9] and community-based participatory research [8,10] and more contemporary frameworks including the National Institute of Minority Heath and Health Disparities (NIMHD) multi-level health disparities framework [11] and the ConNECT framework [12,13]. As illustration, NIMHD's multi-level health disparities framework [11] and (e) prioritizing specialized training as an organizing framework [12,13], all important tenets for addressing SDH through cancer education.…”
mentioning
confidence: 99%